Objects of affect: The domestication of ubiquity. Issue 3 (1st December 2013) - Didakis, Stavros; Phillips, Mike
This article contextualizes digital practices within architectural spaces, and explores the opportunities of experiencing and perceiving domestic environments with the use of media and computing technologies. It suggests methods for the design of reflexive and intimate interiors that provide informational, communicational, affective, emotional and supportive properties according to embedded sensorial interfaces and processing systems. To properly investigate these concepts, a fundamental criterion is magnified and dissected: dwelling, as an important ingredient in this relationship entails the magical power to merge physical environment with the psyche of inhabitants. For this reason, a number of views are presented and discussed, providing necessary conditions to include matters of affectivity, ubiquity and layering complexity of interior space. Moreover, specific processes of the possibilities of the digital are mentioned, and examples are presented of the infusion and diffusion of ubiquitous computing technologies within domestic spaces. To briefly conclude, this article is an attempt to discuss the relationship of human-architecture-computer symbiosis and the design process of creative and innovative spaces that affect states of memory, perception, experience, as well as mood and emotion.